Heuristic mechanism for drone swarm auto-organization - Muñoz, Juan (2018)
Current technology used for fires are: meteorological stations and satellite image and satellites. This last is a great option, but, from space, the fire detection is until it is large enough to be seen from orbital altitude. A drone can be used to monitor a forest looking for fire signs before the satellite observes it, but a single drone to cover a large acre surface is not optimal. A drone swarm with auto-organization capacity, equipped with atmospheric sensors that detect fire hazard conditions or even a fire in an early stage, needs to be used to optimize the area coverage. Implement a heuristic algorithm for drone swarm auto- organization applicable for wildfire alert and detection. Forest fires are a big environmental problem due they are mainly detected until they have burned some square kilometers. When these are detected at the developed stage, the fire will be difficult to contain. Some wildfires affect agricultural along as residential areas causing significant economic loses